PENGARUH RASIO LIKUIDITAS, AKTIVITAS DAN PROFITABILITAS TERHADAP RETURN SAHAM SUB SEKTOR PERBANKKAN BUMN DI BURSA EFEK INDONESIA (BEI) PERIODE 2010-2018 - Deni Sunaryo (Departement of Islamic Banking, Faculty of Islamic Economics and Business, The State of Islamic University (UIN) Sultan Maulana Hasanuddin Banten,, 2020)
This study aims to determine the effect of liquidity ratios, activities, and profitability on stock returns of state-owned banking companies listed on the Indonesia Stock Exchange (IDX) peroide 2010-2018. The method used in this study is a method using a quantitative approach. The research sample taken is an annual financial report obtained from 2010 until 2018 with a probability sampling technique where sampling techniques provide equal opportunities for each popol (member) element to be selected as a sample member. The data analysis technique uses multiple linear regression analysis and hypothesis testing using the SPSS 23. Program tool Based on the results of the study it can be concluded that 1) the liquidity variable does not have a negative and significant effect on stock returns. 2) activity variables have a positive and significant effect on stock returns 3) profitability variables have no significant positive effect on stock returns. 4) the variables of liquidity, activity, and profitability simultaneously (together) have no significant effect on stock returns. Keywords :Ratio Liquidity, Ratio Activity, Ratio Profitability, Stock Return.